Antioxidant and antihypertensive properties of liquid and solid state fermented lentils - Torino, Maria Ines (2013)
The effect of liquid (LSF) and solid state fermentation (SSF) of lentils for production of water-soluble fractions with antioxidant and antihypertensive properties was studied. LSF was performed either spontaneously (NF) or by Lactobacillus plantarum (LP) while SSF was performed by Bacillus subtilis (BS). Native lactic flora in NF adapted better than L. plantarum to fermentative broth and BS counts increased 4.0 log CFU/g up to 48 h of SSF. LSF water-soluble fractions had higher (P ≤ 0.05) free amino groups, GABA content, antioxidant and angiotensin I-converting enzyme inhibitory (ACEI) activities than SSF. In addition, GABA and ACEI activity of LSF increased in a time-dependent manner. Proteolysis by BS was limited, with slight changes in free amino groups, while GABA, total phenolic compounds and antioxidant capacity increased throughout fermentation. Higher antihypertensive potential was observed in NF (96 h) characterised by the highest GABA content (10.42 mg/g extract), ACE-inhibitory potency (expressed as IC50) of 0.18 mg protein/ml and antioxidant capacity of 0.26 mmol Trolox equivalents/g extract. Therefore, water-soluble fermented lentil extracts obtained by LSF are particularly promising as functional ingredients in preventing hypertension.